The Feldstein-Horioka Test of International Capital Mobility : Is it Feasible? - Jansen, W. (IMF Working Papers; Working Paper ;, 1996)
Feldstein and Horioka (1980) argued that the correlation of saving and investment in a cross-section of countries may provide a test of global capital mobility. This paper argues that neither the long-run nor the short-run correlation can serve as a reliable basis for such a test. The intertemporal budget constraint implies that each country's saving and investment should be cointegrated over time. Simulations show that the cross-section regressions used in the literature will produce correlations that strongly tend towards one, regardless of the degree of capital mobility. Although the short-run correlation is not affected by the intertemporal budget constraint, the empirical analysis shows it is primarily a country-specific business cycle fact.